KUALITAS KEGIATAN ADMINISTRASI PENDIDIKAN DI SEKOLAH DAN HUBUNGANNYA DENGAN PENGAWASAN PROFESIONAL - Alauddin Alauddin (Institut Agama Islam Negeri (IAIN) Palopo, 2020)
The quality of education administration carried out by school principals, teachers and staff cannot be separated from supervisory activities carried out by supervisors who are formally appointed by the ministry of national education in a professional manner. The quality functions of educational administration activities that allow quality assurance are supervised by professional supervisors who have a high responsibility attitude.